Universal Thermal Climate Index (UTCI) and adverse pregnancy outcomes in Ahvaz, Iran - Narges Khodadadi; Maryam Dastoorpoor; Narges Khanjani; Afsaneh Ghasemi (BMC, 2022)
Plain Language Summary Scientists have found that climate change has adverse effects on human health. Because pregnant women are one of the most vulnerable groups, these negative impacts may affect their fetuses, which make up the next generation. In this study, we examined the effect of temperature on some pregnancy outcomes, including low birth weight, preterm labor, spontaneous abortion, preeclampsia and gestational hypertension in Ahvaz city, which is one of the hottest cities in the world. One way to assess temperature impact on humans is by using temperature indicators. In this study we used the Universal Thermal Climate Index (UTCI) for this purpose. The data at different time intervals were collected and evaluated with specific models. Our results showed that low values of UTCI, which is equivalent to cold weather, significantly increase the risk of preterm labor. But, high levels of UTCI, which means hot weather, significantly increase the risk of stillbirth. In conclusion; both hot and cold weather can be associated with adverse pregnancy outcomes in Ahvaz city. Therefore, pregnant women should protect themselves from exposure to hot and cold weather.